Gastroesophageal Reflux Disease among Elderly Type 2 Diabetes Mellitus in a Rural Area of Central Sulawesi: A Cross-sectional Study - Kemas Rakhmat Notariza; Nurcholis Nurcholis; Hafiz Yusaryahya; Nanda Santriayu Karimah; Ahmad Yani Mansur; Gunawan Adhiguna; Tri Juli Edi Tarigan (Acta Medica Indonesiana, 2021)
Background: type 2 diabetes mellitus (T2DM) and gastroesophageal reflux disease (GERD) are commonly seen in the geriatric population. This study aimed to investigate the prevalence, risk factors, and alarm-symptoms incidence of GERD among elderly patients with T2DM in a rural area of Central Sulawesi. Methods: this cross-sectional study was conducted from July—September 2019 in Public Health Center of Beteleme, Central Sulawesi. Patients aged ≥60 years old, newly or previously diagnosed with T2DM according to the 2019 American Diabetes Association (ADA) criteria or to the 2015 Indonesian Society of Endocrinology (PERKENI) criteria, were consecutively recruited. We excluded patients being on proton-pump inhibitor or H2-receptor antagonist therapy or having a history of gastric or esophageal surgery. GERD was diagnosed in patients with the score of ≥8 based on the Indonesian version of GERD questionnaire (GERD-Q). Results: among 60 elders with T2DM, 28.3% (95% confidence interval [CI], 16.9-39.7) had GERD. Statistical analysis showed that GERD was significantly associated with consumption frequency of tea (p=0.019) and coffee (p=0.015). No significant relationship was found between gender (p=0.562), obesity (p=0.803), achievement of blood glucose-level control (p=0.478), duration of T2DM (p=0.304), and type of antihyperglycemic drugs (p=0.202) with GERD. Unintentional weight loss was the leading alarm symptom (47.1%; 95%CI, 23.4%-70.8%) found across the GERD group. Conclusion: GERD was prevalent among elderly patients with diabetes. Frequent consumption of either tea or coffee was associated with GERD. Alarm symptoms need further evaluation to screen for complications.